Disentangling the flows of data: Inside or outside the multinational company? - Erik Van der Marel (European Centre for International Political Economy (ECIPE), 2015)
This article aims to investigate the patterns of flows in data around the world. It does so by starting from the proposition that data are used as inputs into the production of services and goods in the economy. Using new BEA input output tables in which data usage has a specific mention, this paper computes data intensities of all 6-digit downstream industry sector activities inside the US. This paper finds that not only are sectors such as telecoms and data processing industries using data most intensively, but that in addition data are heavily used as an input within multinational companies with regards to management decisions and with the aim of administering, overseeing and operating establishments across countries. These results are surprising insofar as most of the policy debate to date has focused on the cross-border movement of personal data which is obtained from the interaction between companies and consumers and not so much on companies using business data that are not necessarily personal. This paper also traces who in the world are the biggest traders of these data-intensive management services and provides a first estimate of how much value-added are traded in management services. In addition, this paper also provides an analysis of which type of countries actually have comparative advantage in trading management services. Finally, a discussion is given on the policy implications regarding the usage of data-intensive services inside firms.
Keywords: F13; F14; F15; F23; O24; 330